Marginalizing Last Mile Logistics Cost through 4th Party Milk Run - Robert de Souza; Linda William; Cher Kian Lee (Advances in Science, Technology and Engineering Systems Journal, 2019)
To reduce its high last mile logistics cost, a company may explore different options such as a horizontal collaboration with another company that has a similar logistics requirement. Traditionally, the collaboration can be conducted through an outsource contract mechanism where the company may need to guarantee a certain number of logistics demands or usage for a fixed period of time. This may incur a fixed transportation and logistics cost for the company. For a company who has more fluctuated logistics demands, it would be difficult to guarantee a certain number of logistics demands or usage for an outsourcing mechanism. The company may end up paying more than it should. Alternatively, the company may want to explore horizontal collaboration with a more flexible contract mechanism such as the “4th party milk run” (4PMR). The 4PMR model leverages on the last mile excess capacity of one company to fulfill the last mile logistics demands for another company based on a pay-per-use arrangement. Using the 4PMR model, the fixed transportation and logistics cost would be translated into a marginal cost. This paper describes the 4PMR model, including the optimization model and its computation experiment on two last mile logistics scenarios. The first scenario is a hypothetical scenario based on our field study in Jakarta, Indonesia with a small number of deliveries, while the second scenario is an actual scenario with a large number of deliveries based on existing routes of a Logistics Service Provider (LSP) in Surabaya, Indonesia. The experiment results show that 4PMR is able to provide a significant reduction in last mile logistics cost. To complement the experiment results, industry perspectives for implementing the 4PMR model is also reviewed.
Keywords: Last mile logistics; Milk run; Excess capacity; Horizontal collaboration; Marginal cost